Long-Term Results of Ultrasound-Guided Radiofrequency Ablation of Benign Thyroid Nodules: State of the Art and Future Perspectives—A Systematic Review - Monpeyssen, Hervé; Alamri, Ahmad; Ben Hamou, Adrien (Frontiers in Endocrinology, 2021)
Background. Nearly 20 years after the first feasibility study, minimally-invasive ultrasound (US)-guided therapeutic techniques are now considered as a safe and effective alternative to surgery for symptomatic benign thyroid nodules. Radiofrequency ablation (RFA) is one of the most widely used treatment in specialized thyroid centers but, due to the relatively recent introduction into clinical practice, there are limited long-term follow-up studies. Aim of our work was to review the outcomes of RFA on solid nonfunctioning and on autonomous thyroid nodules (AFTN) on a long-time period for assessing the results in term of efficacy, complications, and costs and to compare them to the current indications of RFA. Methods. A systematic review was performed using EMBASE and Medline library data. Between 2008 and 2020. 17 studies evaluated RFA for the treatment of benign solid (nonfunctioning or autonomous) thyroid nodules, with an at least 18 months of follow-up. Anthropometric data, safety and efficacy parameters were collected. Results. The majority of the studies were retrospective study and reported 933 nodules, mostly solid. Baseline volume ranged between 6.1±9.6 and 36.3±59.8 mL. Local analgesia was used and the time duration of the treatment was between 5±2 and 22.1±10.9 minutes. The volume reduction rate at 12 months ranged from 67 to 75% for the nodule treated with a single procedure and reached to 93.6±9.7% for nodules treated with repeat ablations. The regrowth rate at 12 months ranged from 0 to 34%. Conclusion. All the studies under examination consistently validated the long-term clinical efficacy and the substantial safety of RFA for the treatment of benign thyroid nodules. Thermal ablation, however, is an operator-dependent technique and should be performed in centers with specific expertise. The selection of the patients should be rigorous because the nodule size and the structural and functional characteristics influence the appropriateness and the outcomes of the treatment. Future perspectives as the treatment of micro-papillary thyroid cancer or cervical recurrence need further investigations.